Dixie betrayed how the South really lost the Civil War - Eicher, David J. 1961- (Little, Brown, 2006)
A study in how governments can self-destruct during wartime. For more than a century, the conventional wisdom has been that the South lost because of overwhelming Union strength and bad luck. The Confederates have been lionized as noble warriors who fought for an honorable cause with little chance of succeeding. But historian Eicher reveals a calamity of political conspiracy, discord, and dysfunction. Drawing on previously unexplored sources, Eicher shows how President Jefferson Davis viciously fought with the Confederate House and Senate, governors, and his own cabinet. Confederate senators threatened each other with physical violence; some were brutal drunks, others, hopeless idealists. Military commanders were assigned not by skill but because of personal connections. Davis frequently interfered with his generals in the field, ignoring the chain of command. Also, some states wanted to set themselves up as separate nations, further undermining efforts to conduct a unified war effort.--From publisher description.
Includes bibliographical references and index
Keywords: Davis, Jefferson <1808-1889>; Davis, Jefferson <1808-1889> -- Military leadership; Geschichte; Politik; Sezessionskrieg (1861-1865); Generals -- Confederate States of America; Political leadership -- Confederate States of America; Sezessionskrieg -- 1861-1865; USA; Confederate States of America -- History; Confederate States of America -- Military policy; Confederate States of America -- Politics and government; United States -- History -- Civil War, 1861-1865 -- Campaigns